Fibroblast Growth Factor-23 Levels Are Associated with Vascular Calcifications in Peritoneal Dialysis Patients - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; KOÇ, MEHMET; TUĞLULAR, ZÜBEYDE SERHAN (KARGER, 2013)
Background: The aim of the study was to assess the relationship between fibroblast growth factor-23 (FGF-23) and vascular calcifications (VC) in peritoneal dialysis (PD) patients. Methods: A cross-sectional study was performed in 55 PD patients who underwent pelvic X-ray to assess for VC. Patients with and without linear calcifications were recorded. Results: Fifteen patients (27.3%) had linear calcifications on pelvic X-ray. FGF-23 levels were higher in patients with VC (299.5 (30.4-2,410.0) vs. 74.4 (14.8-1,030) pg/ml, p < 0.01). Diabetic patients had lower FGF-23 values (43.2 (14.9-134.0) vs. 103.5 (14.8-2,410) pg/ml, p < 0.01). Patients with residual renal function (RRF) had lower FGF-23 levels (70.6 (14.8-513) vs. 179.5 (30.4-2,410) pg/ml, p = 0.06); however, this did not reach statistical significance. FGF-23 levels, age, creatinine, Ca, dialysis duration and HbA1c were positively correlated with VC, whereas RRF, Ca intake and ALP were negatively associated. Multivariate logistic analysis confirmed FGF-23 levels, age, dialysis duration and RRF to be associated with VC. Conclusions: FGF-23 levels are associated with VC in PD patients. Further studies are needed to clarify whether it is simply a marker or a potential factor. It may prove to be an important therapeutic target for VC management. (C) 2013 S. Karger AG, Basel
Keywords: Fibroblast growth factor-23; Vascular calcifications; Peritoneal dialysis; CARDIOVASCULAR RISK; ARTERIAL STIFFNESS; OBESE ADOLESCENTS; FGF-23; THICKNESS; SCORE